Spatial and spatio-temporal distribution of women living with HIV mortality in Porto Alegre, Brazil, from 2007 to 2017 - Maiton Bernardelli; Tonantzin Ribeiro Gonçalves; Marcos Pascoal Pattussi; Nêmora Tregnago Barcellos; Lisiane Acosta (Universidade de São Paulo, 2021)
ABSTRACT OBJETIVE: To present some factors related to the mortality rates of WLHIV in the city of Porto Alegre-RS. METHODS: This is a spatial and spatio-temporal analysis of ecological data about all women monitored by the health care services for the vertical transmission (VT) of HIV, between 2007 and 2017, residing in the city that died during the period. The units of analysis were the 17 sanitary districts of the city. The dependent variable was the mortality rate. The independent territorial variables were the indicators of vulnerability to poverty, women householder proportion, lack of infrastructure, HDI, and GINI index. Still, the individual data collected were: age, race/color, level of education, and period since the HIV diagnosis. The analyses used SPSS 20.0, and QGIS 218.15. RESULTS: Regions with higher vulnerability to poverty and precarious local infrastructure registered higher WLHIV mortality rates, especially black/"pardo" women in fertile age with low education. The regions with most women householders presented a risk of mortality seven times higher. The population with vulnerability to poverty presented the same result. CONCLUSIONS: Regions with critical indicators of vulnerability presented higher mortality rates of WLHIV, which demonstrates social inequalities' impact for these women.